Transcutaneous auricular vagus nerve stimulation improves cortical functional topological properties and intracortical facilitation in patients with Parkinson’s disease - Heng Zhang; Ai-di Shan; Ya-yi Huang; Meng-xi Gao; Chen-hui Wan; Shi-yi Ye; Cai-ting Gan; Hui-min Sun; Xing-yue Cao; Yong-sheng Yuan; Ke-zhong Zhang (npj Parkinson's Disease)
Abstract Our study aimed to investigate the neural mechanisms of taVNS in the motor symptoms of PD, focusing on the topological properties of cortical functional networks and cortical excitability. Thirty-two PD patients underwent functional near‐infrared spectroscopy and transcranial magnetic stimulation evaluation prior to and after two-week taVNS, which were controlled by 20 healthy controls (HCs). PD patients exhibited decreased nodal efficiency (Ne) in the right M1 and increased Ne in the left pre‐motor and supplementary motor area compared with HCs. The decreased Ne in the right M1 was negatively associated with UPDRS-III scores. Interestingly, taVNS treatment improved PD motor symptoms by increasing Ne in the right M1 and enhancing intracortical facilitation (ICF, ISI 10, and 15 ms). The increased Ne and ICF (ISI 15 ms) were negatively correlated with the decreased UPDRS-III scores. taVNS could improve nodal information processing efficiency in the M1 and enhance cortical facilitation to improve PD motor disorders.